Facile synthesis of fibrous Faujasite Y supported Ni (Ni/FFY) catalyst for hydrogen production via glycerol dry reforming - Nornasuha, Abdullah; Nurul Aini, Razali; Herma Dina, Setiabudi; Asmida, Ideris; A. R., Mohamed; A. A., Jalil (Elsevier Ltd, 2023)
In this study, the dendritic structure of Ni-supported Fibrous Faujasite Y (Ni/FFY) catalyst was successfully synthesized by employing a hydrothermal-assisted microemulsion system and subsequently tested in glycerol dry reforming to produce syngas. FFY possesses high porosity due to the formation of radial wrinkle fibre observed from TEM analysis. This provides a huge amount of interparticle pores that facilitate the absorption of the molecules within the material under a minimum hindrance, hence boosting the interior surface accessibility of Ni/FFY. This exclusive morphology contributed to the enhancement in the amount of accessible Ni active sites, resulting in the good activity of Ni/FFY (C3H8O3 conversion = 56.28 %, CO yield = 70.14 %, and H2 yield = 49.80 %). The extraordinary physicochemical properties of Ni/FFY and outstanding catalytic performance in glycerol dry reforming proved its capability as a sustainable catalyst in transforming waste byproduct (glycerol) and greenhouse gas (CO2) to clean energy (H2). This finding presents a pioneering fibrous zeolite catalyst for hydrogen generation in glycerol reforming.